PENGAWASAN TERHADAP BIRO PERJALANAN WISATA ONLINE YANG TIDAK MEMILIKI IZIN DI PROVINSI BALI - Ayu Arsani, Ni Putu; Anom Pemayun, Cok Istri; Dyah Satyawati, Ni Gusti Ayu (Kertha Negara : Journal Ilmu Hukum, 2013)
Travel agency is a business trip planning and tourism services. The increasing of knowledge in the field of technology it is now make many travel agiencies are using online media to conduct the transaction.. Therefore, it is need a supervision by the government against the Travel agency. This paper discuss the issues concerning the government oversight of online Travel agency that does not have a license to operate and remedies that can be taken when fraud or breach of contract occurred. This paper using an empirical legal research. The conclusion of this paper are first, the supervision facing difficulty because of the limitation of the number of the supervising team and the regulation concerning online travel agencies are unclear, which are cause the growth number of the illegal online travel agencies. Second, remedies that can be taken against fraud and breach of contract in an online Travel Agency that does not have a license to operate in the province of Bali.
Keywords: Supervision, Travel Agency, Online